Land redistribution in South Africa : a perspective from the doctrine of creation, theological anthropology and black liberation - Mdingi, Hlulani (University of Pretoria, 2023)
Dissertation (MA (Dogmatics and Christian Ethics))--University of Pretoria, 2022.